State Dependent Pricing and Exchange Rate Pass-Through - Martin Flodén; Fredrik Wilander (Sveriges Riksbank, 2004)
We analyze exchange rate pass-through and volatility of import prices in a dynamic framework where firms are subject to menu costs and decide on price adjustments in response to exchange rate innovations. The exchange rate pass-through and import price volatility then depend on the pricing convention in combination with functional forms of cost and demand functions. In particular, there is lower pass-through, less frequent price adjustments, lower price volatility, and slightly lower average prices when prices are set in the importers currency than when prices are set in the exporters currency. The degree of pass-through also depends on the magnitude of exchange rate innovations. Large exchange rate innovations raise pass-through if prices are set in the importers currency but reduce pass-through if prices are set in the exporters currency. Finally, the presence of inflation can generate a substantial asymmetry in price adjustments. This asymmetry could lead to pitfalls when empirically estimating pass-through, and we present some potential resolutions to this estimation problem.
Keywords: D40; E30; F31; F40; 330; Exchange rate pass-through; Nominal rigidities; Invoicing; State dependent pricing